Effects of modifying mind-body communication technique on communication apprehension of learners visual impairment - Abad, Realiza B.; Magtoto, Frances Olivia M.; Echavia, Darlene D.; Cauyan, Jaclyn Marie L. (Quezon City College of Education, University of the Philippinne Diliman, 2021)
Communication Apprehension (CA), one of the most studied variables in human communication, is defined as the fear of anticipated or real communication with people which results to a variety of anxiety-type feelings such as discomfort, fear, and inadequacy. On the other hand, communication competence refers to the adequate ability to pass along or give information by talking or writing.

Several studies showed the negative correlation of CA and communication competence as well as their relationship with academic achievement of students. This research aimed to find out the level of communication apprehension of Grade 8, 9 and 10 Junior High school students with visual impairment who received support from the Philippine National School for the Blind (PNSB) in Pasay City. The study also sought to determine the effects of modified Mind-Body Communication Technique (M-BCT) in reducing the CA of learners with visual impairment. Single case multiple baseline design across subjects was utilized which involve multiple observations of the behavior of each participant. To determine how the participants may possibly have developed CA, qualitative data about their self-concept was obtained.

On the basis of the results of this research, it can be concluded that participants obtained a low level of communication apprehension after the modified M-BCT. Composition of the pretest and post-test scores in OCA using the T-test revealed that there was a significant decrease in the level of oral communication apprehension of the participants with visual impairment. Furthermore, all multiple baseline graphs show an increasing tend of data outcome in the intervention phase. Future research should continue to examine the level of communication apprehension of visually impaired students across dimensions, age groups, cultures, and schools.
Thesis
Include3s bibliographical references (pages 160-198)
Keywords: Teenagers with visual disabilities -- Education (Secondary) -- Philippines -- Pasay City; Interpersonal communication -- Study and teaching (Secondary) -- Philippines -- Pasay City; Children with visual disabilities -- Education (Secondary) -- Philippines -- Pasay City